Robust correlation technology for online monitoring of changes in the state of the heart by means of laptops and smartphones. (January 2017) - Aliev, T.A.; Rzayeva, N.E.; Sattarova, U.E.
Highlights: Technology for correcting the normalization errors is proposed. 5 informative attributes for monitoring of changes in the state of the heart are given. Concept of the system for heart monitoring in real-time mode is described. Abstract: We demonstrate the possibility of monitoring changes in heart activity through the auscultation and analysis of heart sounds by means of a laptop or smartphone. The proposed technology allows laptop and smartphone users to create bases of reference for informative attributes in the most indicative periods of the day over the course of 10–15 days in home or work environments. During subsequent auscultation of the heart, current combinations of corresponding informative attributes are formed and compared with the reference data. If the current combinations match the reference data, a user is informed that his/her condition is within the norm; otherwise, a recommendation to see a doctor is given.